Role of Canonical Wnt/β-Catenin Pathway in Regulating Chondrocytic Hypertrophy in Mesenchymal Stem Cell-Based Cartilage Tissue Engineering - Wang, Xueqi; Guan, Yiming; Xiang, Shiyu; Clark, Karen L.; Alexander, Peter G.; Simonian, Lauren E.; Deng, Yuhao; Lin, Hang (Frontiers in Cell and Developmental Biology, 2022)
In the past three decades, the cartilage repair potential of mesenchymal stromal cells, or mesenchymal stem cells (MSCs), has been widely examined in animal studies. Unfortunately, the phenotype and physical properties of MSC-derived cartilage tissue are not comparable to native hyaline cartilage. In particular, chondrocytic hypertrophy, a phenotype that is not observed in healthy hyaline cartilage, is concomitant with MSC chondrogenesis. Given that hypertrophic chondrocytes potentially undergo apoptosis or convert into osteoblasts, this undesired phenotype needs to be prevented or minimized before MSCs can be used to repair cartilage injuries in the clinic. In this review, we first provide an overview of chondrocytic hypertrophy and briefly summarize current methods for suppressing hypertrophy in MSC-derived cartilage. We then highlight recent progress on modulating the canonical Wnt/β-catenin pathway for inhibiting hypertrophy. Specially, we discuss the potential crosstalk between Wnt/β-catenin with other pathways in regulating hypertrophy. Lastly, we explore future perspectives to further understand the role of Wnt/β-catenin in chondrocytic hypertrophy.